Analysis of angiogenic and stromal biomarkers in a large malignant mesothelioma cohort. (December 2020) - Chia, Puey Ling; Russell, Prudence; Asadi, Khashi; Thapa, Bibhusal; Gebski, Val; Murone, Carmel; Walkiewicz, Marzena; Eriksson, Ulf; Scott, Andrew M.; John, Thomas
Highlights: Agents targeting angiogenic pathways such as bevacizumab have demonstrated efficacy in mesothelioma. An analysis of the combination of stromal and vascular biomarkers is relevant to the use of multi-angiokinase targets of PDGF, FGF and VEGF in malignant mesothelioma to help determine their prognostic implications. High CD31 was an independent poor prognostic factor and high PDGF-CC expression was associated with poor survival in mesothelioma. There was a high incidence of positive VEGF and FGFR IHC in the large mesothelioma cohort but no significant correlation between prognosis and immune expression was found. Abstract: Background: Malignant mesothelioma (MM) is an aggressive malignancy of the pleura and other mesothelial membranes. Agents targeting vascular endothelial growth factor (VEGF) such as bevacizumab; and multi-kinase inhibitors such as nintedanib [angiokinase inhibitor of VEGF, platelet-derived growth factor (PDGF) receptor and fibroblast growth factor receptor (FGFR)] have recently demonstrated efficacy in MM. Methods: Tissue microarrays (TMAs) were created from formalin-fixed, paraffin-embedded tissue samples obtained from 326 patients with MM who were treated surgically. PDGF-CC, FGFR-1, VEGF and CD31 expression were analysed by immunohistochemical (IHC) staining. The H-score method assigned a score of 0–300 to each sample, based on the percentage of cells stained at different intensities. CD31 was evaluated via Chalkley's method to evaluate microvessel density. We evaluated the association between expression of the biomarkers, clinicopathological factors and outcomes, in patients with MM. Results: CD31 high (≥5) was seen in only 31/302 (10.3%) irrespective of histology. PDGF-CC high (≥150) was seen in 203 /310 (65%) of all samples. VEGF high (≥80) was seen in 219/322 (68%) of all MM with 143/209 (68%) of epithelioid histology. FGFR-1 high (≥40) was seen in 127/310 (41%) of all MM. There was no association of VEGF and FGFR-1 IHC with survival nor differences between histological subtypes. There was a non-significant trend towards poorer survival in epithelioid tumours with increased PDGF-CC expression (OS 18.5 vs 13.2 months; HR 0.7928; 95% CI 0.5958 to 1.055, P = 0.1110). High CD31 score was associated with significantly poorer survival (OS 12 vs 8.6 months; HR 0.48; 95% CI 0.2873 to 0.7941, P = 0.0044). Of the 31 patients with high CD31 scores; 23/31 (74%) were also high for PDGF-CC and 20/31 (64%) with high VEGF scores. CD31 was found to be an independent prognostic factor in multivariate analysis (HR 1.540; 95% CI 1.018 to 2.330; p = 0.041). Conclusions: High CD31 was an independent poor prognostic factor and high PDGF-CC expression was associated with poor survival in MM. Abrogating these pathways may have prognostic implications.